De malas prontas para um destino incerto: a atuação da pastoral do migrante no Ceará Pecém (1995 a 2002) - Sousa, Francisco Amistardam Silva (2019)
The process of capitalist modernization in Ceará was initiated in the “governments of the colonels” and continued in the mid-1980s, when the articulation of the political elite, which was organized at the Ceará Industrial Center (CIC), came to state power with a speech of modernization and breaking of the old practices of traditional clientelism. Political entrepreneurs put in place a market-integrated modernization that, in addition to promoting capitalist accumulation via major infrastructure projects, promoted a disruption in the form of public service contracting and a reduction in staffing. This was the way found by the bourgeoisie, with the political elite of Ceará, for a profound change in the economy from industrialization, causing impacts on the labor force through new forms of employment and income and destruction of the old ways of life found in implanted areas. This accelerated process of modernization of the capitalist relations of production in the state of Ceará, with the state as its main agent, happens in a context of opening the national economy to the foreign market, allowing the attraction of foreign investments for the installation of large infrastructure works such as Pecém Industrial and Port Complex (CIPP), installed on the west coast of the state of Ceará and which has a port terminal and an industrial district, as well as enterprises of the so-called base industry. Our research seeks to investigate the process of capitalist modernization in Ceará, starting from the industrial port modernization taking as a basis the years (1995 - 2002), the period of installation of the Pecém port. We also intend to investigate the actions of the agents directly involved in the process of expropriation of peasant territories around the CIPP. The implementation of the port complex intensified capitalist modernization while deterritorializing communities. The state, captured by capitalist interests, became instrumental in the main agent in promoting the removal of communities and creating the technical objects capable of ensuring the installation of infrastructure. Despite resisting for some time, several families were removed, others were settled in other areas. The attraction of new investments in the industrial area has been presented as the main catalyst in the economic development process in the state of Ceará. The discourse of economic modernization is presented as an alternative to overcome the serious social problems, present in Ceará society, such as the low attendance in essential services, such as education and health and the low rate of formal employment, but it is not what was done to the local communities.